Glucose oxidase and Au nanocluster co-encapsulated metal–organic frameworks as a sensitive colorimetric sensor for glucose based on a cascade reaction. (27th July 2020) - Chi, Jingtian; Guo, Manli; Zhang, Chi; Zhang, Yuanhong; Ai, Shiyun; Hou, Juying; Wu, Peng; Li, Xiangyang
Abstract : The GOx & AuNCs@ZIF-8 composite was simply obtained as a colorimetric glucose sensor with high sensitivity and selectivity and long-term storage stability. Abstract : In this work, glucose oxidase and Au nanoclusters co-encapsulated in zeolitic imidazolate frameworks (GOx & AuNCs@ZIF-8) were obtained by simply mixing Zn 2+, dimethylimidazole, glucose oxidase (GOx) and Au nanoclusters (AuNCs) at room temperature. The GOx & AuNCs@ZIF-8 composite can be used as a sensitive colorimetric sensor for glucose based on the following cascade reaction: GOx converts glucose to gluconic acid and generates H2 O2, which acts as a substrate for AuNCs oxidizing 3, 3′, 5, 5′-tetramethylbenzidine (TMB) to form oxidized TMB (oxTMB) detectable at 652 nm. Owing to the effective cascade reaction and protective effect of the ZIF-8 shell on enzymes, the catalytic activity of GOx & AuNCs@ZIF-8 was enhanced 19.3-fold compared with the free GOx/AuNC solution, and the glucose sensor showed high selectivity and sensitivity. Furthermore, the GOx & AuNCs@ZIF-8 composite showed high long-term storage stability and stability against digesting enzymes and chelating compounds due to the shielding effect of the ZIF-8 scaffold.